PARALLEL STEEL FRAME TECHNIQUE FOR SEISMIC STRENGTHENING OF RC STRUCTURES: CASE STUDY - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2013)
To strengthen reinforced concrete (RC) structures against possible future earthquakes, several techniques are used in practice such as adding new RC shear walls, column jacketing using steel or RC or carbon fibers, adding steel bracing, and using seismic isolation and dampers. To apply these techniques, the whole building or part of it should be evacuated for several months and if this building is a school or a factory it means that the building will lose its function for several months during the strengthening construction. In this paper, parallel braced steel frame strengthening technique is proposed to strengthen the low or middle raise RC structures in which all the construction works are applied from outside of the building and do not affect the building function. The main features of this technique are ensuring the view, ventilation, and sunlight from windows after the retrofitting work is done. Furthermore, using the construction steel members lead to shortening the construction term, improve in quality, and reduce costs. The idea of this technique is to reduce the earthquake displacement demand on the nonductile existing RC structures by attaching steel frames to the building floors. These frames are parallel to the structural system of the building and their foundations are connected to the existing building's foundation. In doing so, it is expected that during an earthquake the building's interstory drifts will reduce in half and prevent building collapse. The parallel steel frames can be designed to the desired limit states using performance-based design method in FEMA or Turkish earthquake code. A study case of a factory building in Turkey is presented. The seismic performance of the building before and after the strengthening was evaluated according to the Turkish earthquake code TERDC-2007. Analysis results indicate the effectiveness of the proposed technique.
Keywords: Seismic; strengthening; earthquake; parallel frame; RC structures